(untitled) (Colombia Medica, 2015)
Objective: Liver transplantation is the treatment of choice for acute and chronic liver failure, for selected cases of tumors, and for conditions resulting from errors in metabolism. This paper reports the experience of a medical center in Latin America. Methods: Were conducted 305 orthotopic liver transplantations on 284 patients between 2004 and 2010. Of these patients, 241 were adults undergoing their first transplantation. Results: The average age of patients was 52 years old, and 62% of the individuals were male. The most common indication was alcoholic cirrhosis. The rate of patient survival after 1 and 5 years was 82 and 72% respectively. The rate of liver graft survival after 1 and 5 years was 78 and 68% respectively. The main cause of death was sepsis. Complications in the hepatic artery were documented for 5% of the patients. Additionally, 14.5% of the patients had complications in the biliary tract. Infections were found in 41% of the individuals. Acute rejection was observed in 30% of the subjects, and chronic rejection in 3%. Conclusion: In conclusion, liver transplantation at our medical center in Colombia offers good mid-term results, with a complication rate similar to that reported by other centers around the world.